Estimating elasticities of demand and supply for South African manufactured exports using a vector error correction model. - Behar, A; Edwards, L (CSAE (University of Oxford), 2004)
Elasticities of demand and supply for South African manufactured exports are estimated using a vector error correction model in order to address simultaneity and non-stationarity issues. Demand is highly price-elastic, with elasticities ranging from –3 to –6. The price elasticity of supply is generally about 1, but some estimates are as low as 0.35. Competitors’ prices and world income are important determinants of demand, but domestic capacity utilization is not an important determinant of export supply. Many different data alternatives are sourced, constructed and estimated, showing the results can be sensitive to the choice of series.